Diversity and distribution of tropical ectomycorrhizal fungi - Corrales, Adriana; Koch, Rachel A.; Vasco-Palacios, Aída M.; Smith, Matthew E.; Ge, Zai-Wei; Henkel, Terry W. (Mycologia, 2022)
The tropics were long considered to have few ectomycorrhizal fungi, presumably due to a paucity of ectomycorrhizal host plants relative to higher-latitude ecosystems. However, an increase in research in tropical regions over the past 30 years has greatly expanded knowledge about the occurrence of tropical ectomycorrhizal fungi. To assess their broad biogeographic and diversity patterns, we conducted a comprehensive review and quantitative data analysis of 49 studies with 80 individual data sets along with additional data from GlobalFungi to elucidate tropical diversity patterns and biogeography of ectomycorrhizal fungi across the four main tropical regions: the Afrotropics, the Neotropics, Southeast Asia, and Oceania. Generalized linear models were used to explore biotic and abiotic influences on the relative abundance of the 10 most frequently occurring lineages. We also reviewed the available literature and synthesized current knowledge about responses of fungi to anthropogenic disturbances, and their conservation status and threats. We found that /russula-lactarius and /tomentella-thelephora were the most abundant lineages in the Afrotropics, the Neotropics, and Southeast Asia, whereas /cortinarius was the most abundant lineage in Oceania, and that /russula-lactarius, /inocybe, and /tomentella-thelephora were the most species-rich lineages across all of the tropical regions. Based on these analyses, we highlight knowledge gaps for each tropical region. Increased sampling of tropical regions, collaborative efforts, and use of molecular methodologies are needed for a more comprehensive view of the ecology and diversity of tropical ectomycorrhizal fungi.